A qualitative exploration of internal power and self-authorship for college students labeled high-risk - Roepnack, BethRené, author; Timpson, William, advisor (Colorado State University. Libraries, 2008)
College students labeled high-risk are often seen in terms of their deficiencies. This study explores the possibility that college students labeled high-risk are able to develop their internal power before college students who are labeled high-privilege. Internal power is defined as the ability to recognize one's power to define one's self and one's world, to create and alter the meaning of one's experiences, attitudes, and values without accepting limits from others or being defined by them. Because students labeled high-risk were found to develop self-authorship-a construct related to internal power-earlier than students considered more privileged (Pizzalato, 2003), it is thought that students labeled high-risk might also recognize their internal power sooner. Using narrative inquiry I explored the internal power, self-authorship development, and epistemological development in 10 college students labeled high-risk. I found that challenging situations pushed the students into making decisions based on their own attitudes, values, and meanings and most of the participants found that they enjoyed such challenging situations. Through such situations the students learned more about themselves and began finding and developing their voice. I also found that all the students were becoming the authors of their lives and seven of them had developed the internal foundations of self-authorship. However, only three of the 10 students had developed epistemologically to the contextual knowing stage that is thought to be required for the development of self-authorship (Baxter Magolda, 2001/2004). I propose that college students labeled high-risk are able to recognize their voice and act on it sooner then college students who are part of the dominant discourse because students labeled high-risk live outside the dominant discourse and already recognize the possibility of multiple discourses. The implications of this proposal for teaching and learning are then discussed.
Keywords: at risk; at-risk students; college students; dominant discourse; narrative inquiry; power; self-authorship; bilingual education; higher education; qualitative research; college students; at risk students